Financial Cycles : What? How? When? - Terrones, Marco (IMF Working Papers; Working Paper, 2011)
This paper provides a comprehensive analysis of financial cycles using a large database covering 21 advanced countries over the period 1960:1-2007:4. Specifically, we analyze cycles in credit, house prices, and equity prices. We report three main results. First, financial cycles tend to be long and severe, especially those in housing and equity markets. Second, they are highly synchronized within countries, particularly credit and house price cycles. The extent of synchronization of financial cycles across countries is high as well, mainly for credit and equity cycles, and has been increasing over time. Third financial cycles accentuate each other and become magnified, especially during coincident downturns in credit and housing markets. Moreover, globally synchronized downturns tend to be associated with more prolonged and costly episodes, especially for credit and equity cycles. We discuss how these findings can guide future research on various aspects of financial market developments.